Poverty is Caused by Low Human Resources - Ading Rahman Sukmara (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Lack of access to quality education, especially primary and secondary education, leads to a lack of skills and knowledge needed to get good jobs. Poor health, caused by lack of access to adequate health services, leads to decreased productivity and the ability to work optimally. Lack of training and opportunities to improve skills, makes it difficult for people to compete in the job market and get better jobs. The low quality of human resources has an impact on economic productivity, so that people's incomes are low and it is difficult to meet their living needs. Poverty can also create an "environment of poverty" that worsens the quality of human resources, because poor children often have difficulty getting proper education and access to adequate health services. Improving the quality of human resources through investment in education, health, and training is the key to overcoming poverty and improving people's welfare. By improving the quality of human resources, people will have more opportunities to get decent jobs, increase their incomes, and meet their living needs.